(untitled) (Marketing Journal, 2025)
The purpose of this article is to develop a strategic plan to enhance the efficiency of logistics services in the Jizzakh Free Economic Zone (FEZ). The study presents an in-depth analysis of the current state and development prospects of the Jizzakh FEZ in the field of logistics, applying PESTLE analysis, GAP analysis, and SWOT analysis. The findings reveal opportunities to increase logistics service efficiency by 40 –85% through the integration of digital technologies (IoT, AI, blockchain), the implementati on of a One -Stop-Shop customs system, and the modernization of transport infrastructure. The proposed strategic planning framework can also be adapted and applied to other free economic zones across the Central Asian region.